Ag / BaSnO3 photocatalyst, preparation method thereof and application of Ag / BaSnO3 photocatalyst in preparation of H2O2

By loading silver (Ag) on ​​perovskite type BaSnO3, the Ag/BaSnO3 photocatalyst was prepared, which solved the problems of high energy input and waste generation during the photocatalytic synthesis of H2O2, and achieved efficient H2O2 generation, and improved the activity and selectivity of the photocatalyst.

CN119608160AActive Publication Date: 2025-03-14GUIZHOU MINZU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411939501.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The prior art has problems with high energy input and waste generation in the process of photocatalytic synthesis of H2O2, and the 2e-WOR path is difficult to achieve, affecting the efficient production of H2O2.

Method used

Silver (Ag) with d10 electron structure is supported on perovskite BaSnO3 to form an Ag/BaSnO3 photocatalyst, prepared by sol-gel method and chemical reduction method, and applied in a photocatalytic system to improve the generation efficiency of H2O2.

Benefits of technology

By loading Ag, the Ag/BaSnO3 photocatalyst forms a Schottky barrier between Ag and BaSnO3, improving the separation efficiency of photogenerated carriers. The Ag load also improves the oxidation capacity of water and significantly improving the H2O2 generation rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608160A_ABST
    Figure CN119608160A_ABST
Patent Text Reader

Abstract

The invention discloses an Ag / BaSnO3 photocatalyst, a preparation method of the Ag / BaSnO3 photocatalyst and application of the Ag / BaSnO3 photocatalyst in preparation of H2O2, belongs to the technical field of photocatalysts, and provides the Ag / BaSnO3 photocatalyst, and the Ag / BaSnO3 photocatalyst is prepared by loading Ag on perovskite type BaSnO3. The invention provides a preparation method of an Ag / BaSnO3 photocatalyst, which comprises the following steps: performing ultrasonic mixing on perovskite type BaSnO3, ultrapure water and AgNO3, and performing first stirring to obtain a premix; dropwise adding a NaBH4 solution, and stirring for the second time to obtain the Ag / BaSnO3 photocatalyst. According to the invention, silver (Ag) with a d10 electronic structure is loaded on perovskite type BaSnO3, and the prepared Ag / BaSnO3 forms a Schottky barrier between Ag and BaSnO3, so that the separation efficiency of photon-generated carriers is effectively improved, and the Ag / BaSnO3 can be used as a photocatalyst for photocatalytic production of H2O2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalysts, and in particular relates to a Ag / BaSnO 3 Photocatalyst and preparation method thereof and use in preparing H 2 O 2 Application in. Background Art

[0002] Hydrogen peroxide (H 2 O 2 As an important chemical and green oxidant, H has been widely used in chemical synthesis, wastewater treatment and textile bleaching. Due to its high energy density and easy transportation, H 2 O 2 It is also considered a promising fuel that can replace fossil fuels. Currently, more than 90% of H 2 O 2 It is produced by indirect oxidation of anthraquinone, but this method has the disadvantages of requiring high energy input and producing a large amount of waste. Therefore, it is necessary to develop low-cost, environmentally friendly H 2 O 2 Large-scale production methods are of great importance.

[0003] H 2 O 2 The photocatalytic synthesis of H 2 O 2 The production process uses oxygen and water as precursors and sunlight as the driving force. 2 O 2 Efficiency, it is important to enhance 2e - Oxygen reduction reaction (ORR) or 2e - Water oxidation reaction (WOR). Due to the upward thermodynamics (1.76 V vs normalized hydrogen electrode, NHE), the light-driven 2e - The WOR pathway is difficult to achieve. 2 O 2 It can act as a hole trap and is easily decomposed during the reaction. Instead, people have been focusing on 2e - O 2 RR route, by adding alcohols to improve H 2 O 2 The alcohol can be oxidized to aldehyde and generate protons. Therefore, the photogenerated electrons can effectively enhance the 2e - O 2 RR half-reaction. At the same time, increase 4e - The WOR process is also a way to improve H 2 O 2 An effective method. 2 Not only 4e- The product of WOR, and it is 2e - O 2 The reactants of the RR process. If the in-situ generated O 2 Can be quickly reduced to H 2 O 2 Therefore, the introduction of highly active and highly selective 2e - ORR sites make the O generated during WOR 2 Rapid reaction with photogenerated electrons is important for improving photocatalytic H 2 O 2 Production efficiency is crucial.

[0004] Loading metal sites on suitable semiconductors can effectively regulate the activity and selectivity of ORR. For example, the prior art has demonstrated that Sb single atoms can promote two-electron ORR by forming μ-peroxides on the Sb sites, and the high concentration of holes on the adjacent N atoms can oxidize water to O. 2 , and then reduced to H 2 O 2 For example, Ni atoms can enhance the 2 absorption, weakening the stability of the OO bond, thereby effectively increasing the 2e - ORR. The existing technology has proved that Au single atom can promote H by inhibiting the dissociation of O-OH* bond. 2 O 2 The generated 2e - O 2 RR transfer pathway. Therefore, it is urgent to construct a new photocatalytic system with a suitable electronic structure to effectively regulate the oxygen absorption mode, the binding energy of the intermediates and the oxygen reduction pathway.

[0005] Silver (Ag) has a unique 10 electronic structure, is considered to be an efficient photocatalytic synthesis of H 2 O 2 Ag is a promising material for the photocatalytic H evolution reaction, which can effectively separate photogenerated carriers and construct reaction centers with high-density electrons / holes. In addition, due to its strong localized surface plasmon resonance (LSPR) effect, Ag modification can effectively improve the efficiency of solar energy utilization. More importantly, Ag is a good material for oxygen evolution reaction and can participate in photocatalytic H 2 O 2 production.

[0006] Perovskite barium stannate (BaSnO 3 ) As an n-type semiconductor material, it has attracted people's attention due to its excellent photoelectric properties. For example, the prior art has developed BaSnO 3Reduced graphene oxide nanocomposites have been used for pollutant degradation. It has been reported that Fe-doped BaSnO 3 It exhibits excellent activity for the photocatalytic oxidation of NO. 3 N 4 / BaSnO 3 Heterojunctions can photocatalyze water decomposition into hydrogen. However, BaSnO 3 There are no reports on the photocatalytic production of hydrogen peroxide. Summary of the invention

[0007] In order to solve the above technical problems, the present invention proposes an Ag / BaSnO 3 Photocatalyst and preparation method thereof and use in preparing H 2 O 2 Application in perovskite BaSnO 3 The upper load has d 10 Electronic structure of silver (Ag) and its application in photocatalytic synthesis of H 2 O 2 , the Ag / BaSnO 3 In Ag and BaSnO 3 A Schottky barrier is formed between the Ag and the Ag, which can effectively improve the separation efficiency of photogenerated carriers. In addition, Ag loading can improve the oxidation capacity of water, produce more oxygen and hydroxyl radicals, which participate in H 2 O 2 The raw materials for the synthesis are photocatalytic H 2 O 2 This provides guidance for the rational design of photocatalysts in production.

[0008] To achieve the above object, the present invention provides a Ag / BaSnO 3 Photocatalyst, the Ag / BaSnO 3 The photocatalyst is a perovskite BaSnO 3 Prepared by loading Ag on it.

[0009] The present invention also provides the Ag / BaSnO 3 The method for preparing a photocatalyst comprises the following steps:

[0010] (1) Perovskite BaSnO 3 , ultrapure water and AgNO 3 Ultrasonic mixing, first stirring, to obtain a premix;

[0011] (2) Add NaBH to the premix obtained in step (1) 4 Solution, second stirring, Ag / BaSnO 3 Photocatalyst.

[0012] Preferably, the perovskite BaSnO 3 , ultrapure water and AgNO 3 The mixing ratio is 0.05-0.15 g: 25-75 mL: 0.00005-0.0075 g; the frequency of the ultrasonic mixing in step (1) is 10-40 kHz, and the time of the ultrasonic mixing is 5-60 min.

[0013] Preferably, in step (1), the rotation speed of the first stirring is 200 to 2000 rpm, and the time of the first stirring is 10 to 30 min.

[0014] Preferably, in step (2), NaBH 4 The amount of solution used is the same as that of the perovskite BaSnO 3 The ratio of dosage is 5-15 mL: 0.05-0.15 g; the NaBH 4 The concentration of the solution is 0.03~0.07M.

[0015] Preferably, in step (2), the rotation speed of the second stirring is 200 to 2000 rpm, and the time of the second stirring is 10 to 30 min.

[0016] Preferably, the perovskite BaSnO 3 The preparation method comprises the following steps:

[0017] S1, BaCl 2 ·2H 2 O and SnCl 4 ·5H 2 O is dissolved in ethylene glycol, then citric acid is added, and stirred at 60-100°C for 1-3 hours to obtain a solution;

[0018] S2, heating the solution obtained in step S1 to 130-170° C. and maintaining for 12-18 hours to obtain a gel;

[0019] S3: The gel obtained in step S2 is calcined at 300-700°C for 2-8h, and then heated to 800-1000°C and maintained for 1-3h to obtain a perovskite BaSnO 3 .

[0020] The present invention also provides the Ag / BaSnO 3 Photocatalyst or Ag / BaSnO prepared by the preparation method 3 Photocatalysts for the preparation of H 2 O 2 Application in.

[0021] The present invention also provides a method for utilizing the Ag / BaSnO3 Photocatalyst preparation of H 2 O 2 The method comprises the following steps:

[0022] Ag / BaSnO 3 The photocatalyst and the methanol solution are mixed to obtain a photocatalyst solution; under the irradiation of a xenon lamp, air is continuously blown into the photocatalyst solution to perform a catalytic reaction, centrifuged, and filtered to obtain H 2 O 2 .

[0023] Preferably, the volume concentration of the methanol solution is 5-15%; the Ag / BaSnO 3 The mixing ratio of the photocatalyst and the methanol solution is 10-30 mg: 25-75 mL; the power of the xenon lamp is 200-400 W; and the time of the catalytic reaction is 0.5 h to 2 h.

[0024] Compared with the prior art, the present invention has the following advantages and technical effects:

[0025] The present invention is based on the perovskite BaSnO 3 The upper load has d 10 The electronic structure of silver (Ag) was synthesized by sol-gel method and chemical reduction method. 3 Photocatalyst. And applied it to photocatalytic synthesis of H 2 O 2 , the Ag / BaSnO 3 In Ag and BaSnO 3 A Schottky barrier is formed between Ag / BaSnO 3 Photocatalytic H production 2 O 2 The rate is 248.9 μmol g -1 h -1 , is pure BaSnO 3 In addition, Ag loading can improve the oxidation capacity of water, generating more oxygen and hydroxyl radicals as the catalysts for H 2 O 2 The raw materials for the synthesis are photocatalytic H 2 O 2 This provides guidance for the rational design of photocatalysts in production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 BaSnO 3 and Ag / BaSnO 3 Morphological characterization of BaSnO 3 SEM images of Ag / BaSnO, scale is 500nm, (b) is 3 SEM images of Ag / BaSnO, scale is 500nm, (c) is 3 EDS images of Ag / BaSnO 3 EDS element diagram;

[0028] Figure 2 To analyze the crystal structure of the catalyst, (a) is BaSnO 3 and Ag / BaSnO 3 XRD spectrum of (b) BaSnO 3 and Ag / BaSnO 3 Infrared spectrum;

[0029] Figure 3 X-ray photoelectron spectroscopy to study Ag / BaSnO 3 Elemental composition and chemical valence states, including high-resolution XPS spectra of (a) Sn 3d, (b) Ba 3d, (c) O1s, and (d) Ag 3d;

[0030] Figure 4 is the photocatalytic activity of different photocatalysts, where (a) is the photocatalytic H 2 O 2 Comparison of generation rates, (b) the effects of different preparation methods on Ag / BaSnO 3 Photocatalytic H 2 O 2 The effect of the generation rate, (c) Ag / BaSnO with different Ag loadings 3 Photocatalytic H 2 O 2 The generation rate, (d) is H 2 O 2 In 0.35%Ag / BaSnO 3 The time course of

[0031] Figure 5 Ag / BaSnO3 Photocatalytic H production 2 O 2 The generation performance of (a) is pure water and 10% CH 3 Comparison of photocatalytic performance in OH, (b) the effect of light source on photocatalytic performance;

[0032] Figure 6 The photochemical properties of the prepared catalysts, where (a) is the UV–vis diffuse reflectance spectrum and (b) is the BaSnO 3 PL spectrum of

[0033] Figure 7 The electrochemical properties of the prepared catalysts are tested, where (a) is the EIS spectrum of the prepared photocatalyst, (b) is the LSV curve of the prepared photocatalyst, and (c) is the BaSnO 3 Mott-schottky curve, (d) is Ag-BaSnO 3 Mott-schottky curve;

[0034] Figure 8 Ag / BaSnO 3 Photocatalytic H production 2 O 2 The formation mechanism of Ag / BaSnO was studied, where (a) is the effect of different scavengers on the Ag / BaSnO 3 Photocatalytic H production 2 O 2 The influence of (b) is Ag / BaSnO 3 Photocatalytic H production 2 O 2 mechanism. DETAILED DESCRIPTION

[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0038] Without departing from the scope or spirit of the present invention, various modifications and variations may be made to the specific embodiments of the present invention description, which will be apparent to those skilled in the art. Other embodiments obtained from the present invention description will be apparent to those skilled in the art. The present invention description and examples are merely exemplary. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art, and the raw materials used are all commercially available commodities.

[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0040] Example 1

[0041] S1, 2mmol BaCl 2 ·2H 2 O and 2 mmol SnCl 4 ·5H 2 O was dissolved in 5 mL of ethylene glycol, and then 20 mmol of citric acid was added and stirred at 80 °C for 2 h to obtain a solution;

[0042] S2, the solution is heated to 150°C and maintained for 15 hours to obtain a gel;

[0043] S3, the gel was calcined at 500℃ for 5h, then heated to 900℃ and kept for 2h to obtain perovskite BaSnO 3 .

[0044] (1) 0.1 g perovskite BaSnO 3 , 50 mL ultrapure water and 0.0010 g AgNO 3 (AgNO 3 The dosage is perovskite BaSnO 3 1% by mass), 20kHz ultrasonic mixing for 30min, 600rpm first stirring for 20min to obtain a premix;

[0045] (2) Add 10 mL of 0.05 M NaBH to the premix. 4Solution, 600rpm second stirring for 20min, 9000rpm, 25℃ centrifugation for 5min, 10 -2 Pa vacuum degree, 50℃ vacuum drying for 12h, Ag / BaSnO 3 Photocatalyst.

[0046] Utilizing Ag / BaSnO 3 Photocatalyst preparation of H 2 O 2 The method comprises the following steps: in a 100 mL beaker, 20 mg Ag / BaSnO 3 The photocatalyst was dispersed in 50 mL of a 10% methanol solution by ultrasonic treatment at 20 kHz for 10 min to obtain a photocatalyst solution. Under irradiation with a 300 W xenon lamp, air was continuously blown into the photocatalyst solution for 2 h of catalytic reaction. The solution was centrifuged at 9000 rpm and 25 ° C for 3 min, and the supernatant was taken to obtain H 2 O 2 .

[0047] Example 2

[0048] S1, 2mmol BaCl 2 ·2H 2 O and 2 mmol SnCl 4 ·5H 2 O was dissolved in 5 mL of ethylene glycol, and then 20 mmol of citric acid was added and stirred at 60 °C for 3 h to obtain a solution;

[0049] S2, the solution is heated to 130°C and maintained for 18 hours to obtain a gel;

[0050] S3, the gel was calcined at 300℃ for 8h, then heated to 800℃ and maintained for 3h to obtain perovskite BaSnO 3 .

[0051] (1) 0.1 g perovskite BaSnO 3 , 25 mL ultrapure water and 0.0020 g AgNO 3 (AgNO 3 The dosage is perovskite BaSnO 3 2% by mass) 20kHz ultrasonic mixing for 30min, 600rpm first stirring for 10min to obtain a premix;

[0052] (2) Add 5 mL of 0.05 M NaBH to the premix. 4 Solution, 600rpm second stirring for 10min, 9000rpm, 25℃ centrifugation for 5min, 10 -2 Pa vacuum degree, 60℃ vacuum drying for 12h, Ag / BaSnO 3 Photocatalyst.

[0053] Utilizing Ag / BaSnO 3 Photocatalyst preparation of H 2 O 2 The method comprises the following steps: in a 100 mL beaker, 10 mg Ag / BaSnO 3 The photocatalyst was ultrasonicated at 20kHz for 5 minutes and dispersed in 20mL of a 10% methanol solution to obtain a photocatalyst solution. Under the irradiation of a 200W xenon lamp, air was continuously blown into the photocatalyst solution for catalytic reaction for 2 hours. The solution was centrifuged at 9000rpm and 25℃ for 3 minutes, and the supernatant was taken to obtain H 2 O 2 .

[0054] Example 3

[0055] S1, 2mmol BaCl 2 ·2H 2 O and 2 mmol SnCl 4 ·5H 2 O was dissolved in 5 mL of ethylene glycol, and then 20 mmol of citric acid was added and stirred at 100 °C for 1 h to obtain a solution;

[0056] S2, the solution is heated to 170°C and maintained for 12 hours to obtain a gel;

[0057] S3, the gel was calcined at 700℃ for 2h, then heated to 1000℃ and maintained for 1h to obtain perovskite BaSnO 3 .

[0058] (1) 0.1 g perovskite BaSnO 3 , 75 mL ultrapure water and 0.0050 g AgNO 3 (AgNO 3 The dosage is perovskite BaSnO 3 5% by mass) by 20kHz ultrasonic mixing for 40min, and first stirring at 600rpm for 30min to obtain a premix;

[0059] (2) Add 15 mL of 0.05 M NaBH to the premix. 4 Solution, 200rpm second stirring for 30min, 9000rpm, 25℃ centrifugation for 5min, 10 -2 Pa vacuum degree, 60℃ vacuum drying for 12h, Ag / BaSnO 3 Photocatalyst.

[0060] Utilizing Ag / BaSnO 3 Photocatalyst preparation of H 2 O 2The method comprises the following steps: in a 100 mL beaker, 30 mg Ag / BaSnO 3 The photocatalyst was ultrasonicated at 20kHz for 10min and dispersed in 75mL of a 10% methanol solution to obtain a photocatalyst solution. Under irradiation with a 400W xenon lamp, air was continuously blown into the photocatalyst solution for 2h of catalytic reaction. The solution was centrifuged at 9000rpm and 25℃ for 3min, and the supernatant was taken to obtain H 2 O 2 .

[0061] Experimental example

[0062] 1.1 Materials used in the experiment

[0063] Barium chloride (BaCl 2 , 99.5%), tin chloride pentahydrate (SnCl 4 ·5H 2 O, 99%), citric acid (C 6 H 8 O 7 , 99.5%), p-benzoquinone (p-BQ, >99.8%), potassium hydrogen phthalate (C 8 H 5 KO 4 ,>99.8%), potassium iodide (KI,>99.8%), sodium borohydride (NaBH 4 , 95%), sodium sulfate (Na 2 SO 4 ,>99.8%), ethylene glycol (C 2 H 6 O 2 , 99%), silver nitrate (AgNO 3 , 99.5%).

[0064] Ag / BaSnO used 3 The photocatalyst is Ag / BaSnO prepared in Example 1. 3 Photocatalyst.

[0065] 1.2 Characterization

[0066] The Ag / BaSnO prepared in Example 1 was observed by scanning electron microscopy (SEM, ZEISS Sigma 300). 3 The morphology of the photocatalyst was studied.

[0067] The Ag / BaSnO prepared in Example 1 was analyzed by X-ray diffractometer (XRD, Rigaku SmartLab SE). 3 The crystal phase of the photocatalyst was analyzed.

[0068] The chemical composition and chemical state of the samples were analyzed by X-ray photoelectron spectroscopy (XPS, Thermo-Scientific K-Alpha).

[0069] The Ag / BaSnO prepared in Example 1 was studied by Fourier transform infrared spectroscopy (FTIR, Thermo-Scientific Nicolet iS10). 3 Structure of the photocatalyst.

[0070] The light absorption was analyzed by UV-vis DRS (Shimadzu UV-2600). The separation ability of the sample photocatalytic carrier was studied by fluorescence spectrometer (PL, Edinburgh instruments Ltd. FLS980).

[0071] On an electrochemical workstation (Chenhua, CHI660D), Pt wire was used as the counter electrode, FTO conductive glass loaded with photocatalyst was used as the working electrode, and saturated calomel electrode was used as the reference electrode. 2 SO 4 Electrochemical performance tests were carried out in the experiment. Electrochemical impedance spectroscopy was performed at an open circuit potential of 0.1 to 105 Hz. Mott–Schottky curves were performed in the potential range of -0.5 V to 0.5 V, at frequencies of 1000 Hz, 1500 Hz, and 2000 Hz. The voltage scanning range of the linear sweep voltammetry curve was -0.5 to 1.3 V, and the scanning rate was 0.01 V s -1 .

[0072] 1.3 Photocatalytic test

[0073] In a 100mL beaker, 20mgAg / BaSnO 3 The photocatalyst was ultrasonically dispersed (ultrasonic parameters 20kHz, 10min) in 50mL of a 10% methanol solution to obtain a photocatalyst solution; under irradiation with a 300W xenon lamp, air was continuously bubbled into the photocatalyst solution for catalytic reaction for 2h, centrifuged at 9000rpm, 25°C for 3min, filtered using a 0.22μm filter membrane, and the supernatant was taken to detect the concentration of hydrogen peroxide.

[0074] The iodine titration method was used to detect H 2 O 2 The supernatant was diluted to 2 mL and 0.1 M potassium hydrogen phthalate (C 8 H 5 KO 4 ) and 0.4 M potassium iodide (KI) in a 2 mL mixed solution. After reacting for 30 min, the absorbance was measured at a wavelength of 350 nm, and H was determined according to the following equation:2 O 2 Concentration: H 2 O 2 +3I - +2H→I 3 - +2H 2 O.

[0075] 2.1 Characterization of photocatalysts

[0076] The Ag / BaSnO prepared in Example 1 was characterized by scanning electron microscopy. 3 Surface morphology of photocatalysts. Figure 1 The BaSnO prepared in Example 1 3 The Ag / BaSnO prepared in Example 1 3 SEM image of Figure 1 As can be seen in (a), BaSnO 3 It presents a needle-like morphology with a size ranging from a few hundred nanometers to a few micrometers. 3 The surface is loaded with many nanoparticles (such as Figure 1 (b)). EDS (e.g. Figure 1 (c)) and EDS element map (e.g. Figure 1 (d) shows that O, Ba, Sn and Ag elements are uniformly dispersed in the obtained Ag / BaSnO 3 middle.

[0077] The Ag / BaSnO prepared in Example 1 was analyzed by X-ray diffraction. 3 The crystal structure of the photocatalyst. Figure 2 As shown in (a), the diffraction peaks are located at 30.7°, 43.9°, 54.6°, 63.9°, and 72.5°, corresponding to cubic BaSnO 3 (PDF#15-0780) with (110), (200), (211), (220) and (311) planes. This indicates that cubic perovskite BaSnO 3 In Ag / BaSnO 3 There is no characteristic peak of Ag in the sample, which is because the Ag content is too low to be detected.

[0078] The Ag / BaSnO prepared in Example 1 was characterized by Fourier transform infrared spectroscopy (FTIR). 3 The structure of the photocatalyst was characterized. Figure 2 As shown in (b). Among them, 628cm -1 The characteristic peaks are attributed to SnO 6 Symmetrical stretching vibration, 650cm -1The absorption peak at 1443cm -1 The peak is attributed to the stretching vibration of the Ba-O bond. -1 and 1610cm -1 The two absorption peaks at , are attributed to the stretching vibration and bending vibration of hydroxyl groups. 3 and BaSnO 3 At 4000cm -1 ~400cm -1 The results show that the perovskite BaSnO 3 , the loading of Ag on BaSnO 3 The structure has little impact.

[0079] The Ag / BaSnO prepared in Example 1 was studied by X-ray photoelectron spectroscopy (XPS). 3 The composition and chemical valence of the elements in Figure 3 As shown in Figure 2, the prepared samples contain Sn, Ba, O, Ag and C. The high-resolution spectrum of Sn 3d (e.g. Figure 3 (a) consists of two peaks at 494.7eV and 486.3eV, which are attributed to Sn 3d 3 / 2 and Sn 3d 5 / 2, respectively. The binding energy difference between Sn3d 3 / 2 and Sn 3d 5 / 2 is 8.45eV, indicating that the valence state of Sn is +4. From the high-resolution ( Figure 3 As can be seen in (b), the binding energies of 794.9 eV and 779.5 eV are attributed to Ba 3d 3 / 2 and Ba 3d 5 / 2. Figure 3 (c) is divided into four peaks at 533.0 eV, 531.2 eV, and 530.3 eV, which are attributed to absorbed oxygen, oxygen vacancies, and lattice oxygen. The high resolution of Ag3d (e.g. Figure 3 (d) shows that the peaks at 373.2 eV and 367.3 eV are attributed to Ag 3d 3 / 2 and 3d 5 / 2 of Ag, and the peak difference of 6.0 eV indicates that Ag is Ag. 0 exists in the form of.

[0080] 2.2 Evaluation of photocatalytic performance of photocatalysts

[0081] In 10% CH 3 OH and O 2 In the presence of 2 O 2 The photocatalytic activity of the prepared photocatalyst was evaluated by the generation rate of Figure 4 (a) shows the generation of H using different photocatalysts.2 O 2 The rate of stannate photocatalyst (BaSnO 3 and SrSnO 3 ) can effectively convert O 2 Photocatalytic reduction to H 2 O 2 ,BaSnO 3 H 2 O 2 Production amount (33.1 μmol g -1 h -1 ) is higher than SrSnO 3 (13.5 μmol g -1 h -1 ). The introduction of co-catalysts such as Ni and NiO reduces the 2 O 2 The generation rate of H 2 O 2 In order to study the effect of the preparation method of silver on H 2 O 2 The photocatalytic reduction and chemical reduction methods were used to reduce the generation rate of BaSnO 3 Silver is deposited on the surface. Both methods can effectively improve the H 2 O 2 The generation rate of NaBH 4 Ag prepared by reduction method has higher H 2 O 2 The generation rate is obtained by the method used in the present invention. 4 Ag, H synthesized by chemical reduction 2 O 2 The generation rate has increased by more than 4 times (such as Figure 4 (b)). The effect of silver content on photocatalytic activity was studied. Figure 4 As can be seen from (c), when the Ag content increases from 0 to 0.35%, H 2 O 2 The formation rate increases. As the Ag content further increases, the formation rate gradually decreases. This is because the appropriate amount of Ag can effectively promote the separation of photogenerated carriers, while the excess Ag covers the BaSnO 3 active center, leading to H 2 O 2 The generation rate of Figure 4 (d) is BaSnO 3 and 0.35%Ag / BaSnO 3 Upper H 2 O 2The curve of the generation rate changing with time. The results show that with the extension of time, H 2 O 2 The concentration of Ag / BaSnO 3 When the mass fraction is greater than 0.35%, H 2 O 2 The generation rate is higher than that of BaSnO 3 .

[0082] The results were compared in pure water and 10% CH 3 Photocatalytic H 2 O 2 The generation performance of Figure 5 As shown in (a), in pure water, H 2 O 2 Can be formed on the surface, H 2 O 2 In BaSnO 3 and Ag / BaSnO 3 The formation rates on -1 h -1 and 70.6 μmol g -1 h -1 In 10% methanol solution, H 2 O 2 The generation rates of -1 h -1 and 248.9 μmol g -1 h -1 This is because CH 3 OH can act as a sacrificial agent for photogenerated holes, generating more free electrons that can react with O 2 The reaction generates H 2 O 2 The influence of light source was studied and the results are as follows. Figure 5 As shown in (b). Under visible light irradiation, BaSnO 3 and Ag / BaSnO 3 Upper H 2 O 2 The generation rates were 23.4 μmol g -1 h -1 and 43.8 μmol g -1 h -1 . Full spectrum excitation can improve H 2 O 2 The generation rate is because the higher the utilization rate of light, the more H 2 O 2 The more photogenerated carriers are generated.

[0083] The photoelectric properties of photocatalysts determine their photocatalytic performance. 3 and Ag / BaSnO 3 The reasons for the different photocatalytic activities were investigated in detail on the photoelectric properties of the prepared samples.

[0084] The light absorption of photocatalysts is an important factor affecting the photocatalytic activity. The light response range of the samples was studied by UV-visible diffuse reflectance spectroscopy. Figure 6 As shown in (a), BaSnO 3 and Ag / BaSnO 3 The absorption band edge of BaSnO is about 410nm. According to the Tauc equation, 3 and Ag / BaSnO 3 The band gaps of BaSnO and Ag are 3.06eV and 3.01eV respectively. This shows that the introduction of Ag can reduce the 3 The band gap width, that is, the introduction of Ag can effectively improve the utilization rate of solar energy and generate more carriers.

[0085] The photogenerated carriers of the samples were studied by photoluminescence spectroscopy (PL). The weaker the photoluminescence intensity, the higher the efficiency of photogenerated carrier separation. Figure 6 As shown in (b), Ag / BaSnO 3 The luminescence intensity is significantly lower than that of BaSnO 3 , indicating that Ag / BaSnO 3 It has a stronger ability to separate photogenerated carriers. Therefore, Ag modification can improve the separation efficiency of photogenerated carriers.

[0086] In order to study the Ag / BaSnO 3 The interfacial electrochemical properties of 0.5 M Na 2 SO 4 Electrochemical impedance spectroscopy (EIS) tests were performed. Figure 7 (a) is the electrochemical impedance spectroscopy (EIS) of the synthesized photocatalyst. 3 The semicircle arc is larger than BaSnO 3 The semicircle of is small, indicating that the deposition of Ag is conducive to the transfer of electrons. The effect of Ag on water oxidation activity was studied by linear sweep voltammetry (LSV). Figure 7 (b) provides the LSV curve of the prepared photocatalyst. From the LSV curve, Ag / BaSnO 3 BaSnO 3 It showed higher water oxidation activity, indicating that the water oxidation ability was improved after Ag deposition. At the same time, it was found that there was an oxidation peak at 0.24 V, which was due to the oxidation of Ag.

[0087] The Mott-schottky curves at 500, 1000 and 1500 Hz were measured to explore the 3 and Ag / BaSnO 3 The best semiconductor properties. Figure 7 (c) and Figure 7 As shown in (d), they all show C -2 The positive slope of the value (relative to the applied potential) indicates that BaSnO 3 and Ag / BaSnO 3 It is an n-type semiconductor. BaSnO 3 The flat band value is -0.55V, Ag / BaSnO 3 The flat band value of BaSnO is -0.38 V. Therefore, the flat band potential after Ag modification has a positive shift. Since the conduction band potential is close to the flat band, the valence band can be based on the 3 and Ag / BaSnO 3 The band gap energy of BaSnO 3 and Ag / BaSnO 3 The band gap energy of BaSnO is basically the same. After Ag modification, 3 The valence band energy of BaSnO increases by 0.1 V. 3 Compared with Ag / BaSnO 3 The oxidation ability of water is stronger, H 2 O 2 Higher spawn rate.

[0088] Study on photocatalytic H 2 O 2 The main active species in the process are crucial for understanding the photocatalytic H 2 O 2 The formation mechanism of ethylenediaminetetraacetic acid disodium, isopropanol and p-benzoquinone are used to capture holes (h+), superoxide anions (·O 2- ) and hydroxyl radical (·OH) active species. Figure 8 As shown in (a), after adding disodium ethylenediaminetetraacetate, isopropanol and p-benzoquinone into the photocatalytic system, H 2 O 2 The generation rate of superoxide radicals decreased. p-Benzoquinone was introduced into the photocatalytic system. Therefore, it can be concluded that superoxide radicals are H 2 O 2 The necessary conditions for the formation of holes (h+), superoxide anions (·O 2- ) and hydroxyl groups (·OH) participate in the H 2 O 2 On this basis, BaSnO 3 Possible formation mechanism of hydrogen peroxide produced by photocatalysis ( Figure 8(b)). Under light, electrons are excited to BaSnO 3 The lowest unoccupied molecular orbital (LUMO) of the photon is generated, while the holes are retained in the highest occupied molecular orbital (HOMO) and generate photogenerated carriers, namely photogenerated holes and electrons. The holes can react with the adsorbed water to generate O 2 and OH. 2 is reduced to superoxide radicals, which react with two electrons and two protons to generate H 2 O 2 . Because Ag and BaSnO 3 The difference between them can form a Schottky barrier, and electrons transfer from Ag to BaSnO 3 , promoting the separation of photogenerated carriers, and more free electrons participate in H 2 O 2 In addition, BaSnO 3 The valence band of H is increased, and the oxidation of water is enhanced. Therefore, Ag modification increases the 2 O 2 The generation rate.

[0089] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. An Ag / BaSnO3 photocatalyst, characterized in that: The Ag / BaSnO3 photocatalyst is prepared by loading Ag on perovskite-type BaSnO3.

2. The method for preparing the Ag / BaSnO3 photocatalyst according to claim 1, characterized in that: The following steps are involved: (1) Perovskite-type BaSnO3, ultrapure water and AgNO3 are ultrasonically mixed and first stirred to obtain a premix; (2) NaBH4 solution is added dropwise to the premix obtained in step (1), and stirred for a second time to obtain Ag / BaSnO3 photocatalyst.

3. The preparation method according to claim 2, characterized in that: The mixing ratio of the perovskite BaSnO3, ultrapure water and AgNO3 in step (1) is 0.05-0.15g:25-75mL:0.00005-0.0075g; the frequency of the ultrasonic mixing in step (1) is 10-40kHz, and the time of the ultrasonic mixing is 5-60min.

4. The preparation method according to claim 2, characterized in that: In step (1), the first stirring speed is 200 to 2000 rpm, and the first stirring time is 10 to 30 min.

5. The preparation method according to claim 2, characterized in that: The ratio of the amount of the NaBH4 solution used in step (2) to the amount of the perovskite-type BaSnO3 used in step (1) is 5-15 mL: 0.05-0.15 g; the concentration of the NaBH4 solution in step (2) is 0.03-0.07 M.

6. The preparation method according to claim 2, characterized in that: In step (2), the rotation speed of the second stirring is 200 to 2000 rpm, and the time of the second stirring is 10 to 30 minutes.

7. The preparation method according to claim 2, characterized in that: The method for preparing the perovskite-type BaSnO3 in step (1) comprises the following steps: S1, BaCl2·2H2O and SnCl4·5H2O are dissolved in ethylene glycol, and then citric acid is added and stirred at 60-100°C for 1-3h to obtain a solution; S2, heating the solution obtained in step S1 to 130-170° C. and maintaining for 12-18 hours to obtain a gel; S3. The gel obtained in step S2 is calcined at 300-700° C. for 2-8 hours, and then heated to 800-1000° C. and maintained for 1-3 hours to obtain perovskite-type BaSnO3.

8. Use of the Ag / BaSnO3 photocatalyst according to claim 1 or the Ag / BaSnO3 photocatalyst prepared by the preparation method according to any one of claims 2 to 7 in the preparation of H2O2.

9. A method for preparing H2O2 using the Ag / BaSnO3 photocatalyst according to claim 1, characterized in that: The following steps are involved: Ag / BaSnO3 photocatalyst and methanol solution are mixed to obtain a photocatalyst solution; under the irradiation of a xenon lamp, air is continuously blown into the photocatalyst solution to perform a catalytic reaction, and the solution is centrifuged and filtered to obtain H2O2.

10. The method for preparing H2O2 according to claim 9, characterized in that: The volume concentration of the methanol solution is 5-15%; the mixing ratio of the Ag / BaSnO3 photocatalyst and the methanol solution is 10-30 mg: 25-75 mL; the power of the xenon lamp is 200-400 W; and the time of the catalytic reaction is 0.5-2 h.

Citation Information

Patent Citations

  • Novel perovskite composite photocatalyst and application thereof

    CN113877575A

  • Defect-poor barium hydroxystannate perovskite photocatalyst as well as preparation method and application thereof

    CN115414927A